Preliminary paleomagnetic studies of lake sediments in Eastern Canada - Mott, R.; Foster, J. (Géographie physique et Quaternaire, 1977)
Nine lake bottom sediment cores from small lakes in Eastern Canada, three of which were oriented to an azimuth, have been analyzed magnetically in an attempt to delineate the paleomagnetic character of the late-Pleistocene and Holocene sediments as an aid to stratigraphy and chronology. Secular variations are discernable in mineral sediments and in overlying organic sediments when intensities are strong enough to produce reliable results. Where organic content was high and intensities low, erratic results were obtained. Short segments of some cores, involving at most several centimetres, showed negative values for inclination, but whether or not these can be related to magnetic reversals or excursions or are spurious results, cannot be determined at this time.